Occurrence Characteristics and Threshold Pore Throat Radius of Movable Fluids for Dolomite Intercrystalline Pores of Lacustrine Carbonate Rocks - Shiming Zhang; Xiaojun Zhang; Tingjing Zhang; Yongxian Zheng; Jun Cui; Juerong Fu; Chao Wang; Xiaofeng Yu (Geofluids)
The reservoir evaluation and classification are restrained by the progress of research on the pore structure and fluid occurrence in dolomite intercrystalline pores of the Paleogene lacustrine carbonate rock in the western Qaidam Basin. The experimental method adopted to investigate the fluid occurrence of the lacustrine carbonate rock in the study area can be used as a reference for studying tight reservoirs. By integrating technical approaches such as the thin-section petrographic analysis, SEM, electron probe, mercury injection test, and NMR test, this research studies the petrology, pore type and distribution, and pore structure of the reservoir. Moreover, the pore fluid distribution and threshold pore throat radius for the distribution of movable fluids are investigated by integrating the centrifuging treatment and NMR characterization. Results show that pores of samples in the study area are dolomite intercrystalline pores, intercrystalline dissolved pores, framework dissolved pores of algal limestone (dolostone), dissolved pores of saline minerals, and interlayer fractures, among which dolomite intercrystalline pores and intercrystalline dissolved pores are found with the highest proportions (60%). The dolomite intercrystalline pores and intercrystalline dissolved pores are nano-micropore throats with a narrow distribution. Their capillary pressure curve is characterized by a high plateau and negative skewness, while the NMR relaxation time spectrum is left-skewed and presents higher bond water saturation (over 65%). For intercrystalline pores and intercrystalline dissolved pores, the main storage space for movable fluids is provided by small and medium pores (corresponding to the NMR relaxation time of 1–10 ms and 10–100 ms, respectively), and the experimentally determined threshold pore throat radius for movable fluids is 47 nm. The reservoir is hydrophilic and therefore movable fluids mainly occur in the centers of pores. The samples with higher proportions of coarse pores and pore connectivity are associated with higher proportions of movable fluids. Our analysis shows the dolomite intercrystalline pore has a certain storage capacity and yet inferior connectivity; the proportion of movable fluids that can effectively flow is key to evaluating the effectiveness of reservoirs with dolomite intercrystalline pores.